2007
DOI: 10.4103/0970-4388.31986
|View full text |Cite
|
Sign up to set email alerts
|

Cherubism in siblings: A case report

Abstract: Cherubism is a benign disease of bones affecting the jaws and giving a characteristic cherubic appearance to the patient. On radiography, the lesions exhibit bilateral multilocular radiolucent areas. Histopathology shows numerous multinucleated giant cells in the background of proliferating fibrous connective tissue. Cherubism can be a solitary case. The present report describe cherubism in two siblings and briefly review the literature on this subject.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In addition to genetic factors, Caballero and Vinals [14] indicated other possible causes of cherubism such as mesenchymal alterations during jaw development, an odontogenic origin or even hormonal and traumatic factors. Today we know that a mutation in the gene encoding SH3BP2 plays a role in the disease [6,7,10,11,21]. There are indications that the gene SH3BP2 plays a role in regulating the increased osteoblast and osteoclast activities that are seen in normal tooth eruption, and point mutations in the gene could cause pathologic activation of osteoclasts [21, 31,36].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to genetic factors, Caballero and Vinals [14] indicated other possible causes of cherubism such as mesenchymal alterations during jaw development, an odontogenic origin or even hormonal and traumatic factors. Today we know that a mutation in the gene encoding SH3BP2 plays a role in the disease [6,7,10,11,21]. There are indications that the gene SH3BP2 plays a role in regulating the increased osteoblast and osteoclast activities that are seen in normal tooth eruption, and point mutations in the gene could cause pathologic activation of osteoclasts [21, 31,36].…”
Section: Resultsmentioning
confidence: 99%
“…A molecular pathogenesis of cherubism has been proposed, with the detection of a mutation in the gene encoding SH3 - binding protein 2 (SH3BP2) [6,10,31] and possible degradation of the Msx-1 gene which is involved in the regulation of mesenchymal interaction during craniofacial morphogenesis [11]. It is believed that the different clinical manifestations of cherubism are due to the changes secondary to mutations or incomplete penetrance [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Its pathogenesis is unknown but heredity plays an important role. 2,3 Some studies have reported cherubism to be a family pathology; however, both hereditary and nonhereditary cases have been described. 4,5 In this patient, there was no history of the disease in any of the family members, and therefore, it was a nonfamilial case.…”
Section: Discussionmentioning
confidence: 99%
“…A molecular pathogenesis of cherubism has been proposed, with the detection of a mutation in the gene encoding SH3BP2[123] and possible degradation of the Msx-1 gene, which is involved in the regulation of mesenchymal interaction during craniofacial morphogenesis. [4] The most accepted theory regarding the pathogenesis of cherubism is its association with an autosomal dominant gene, i.e., family inheritance.…”
Section: Case Reportmentioning
confidence: 99%